ANALYSIS OF NON-VERBAL EXPRESSION IN THE “TIMUN EMAS” DRAMA PERFORMANCE FOR CHILDREN AGED 10–18 YEARS AT FASTI (FORUM ANAK SAMBIREJO TIMUR) - Fadhillah, Rizka; Kristiana, Vera; Sopha, Diana (Fakultas Sastra UMN AL Washliyah, 2025)
This article analyzes nonverbal communication in the drama performance of Timun Emas at the Children's Forum (FASTi) in East Sambirejo. The aim is to understand how nonverbal expressions such as gestures, facial expressions, posture, eye contact, and intonation contribute to the delivery of moral messages to children aged 10–18. Using qualitative descriptive methods, the data were collected through observation, interviews, and documentation. The findings suggest that nonverbal communication effectively supports children's understanding of the storyline and values such as courage, compassion, and creativity. This study highlights the educational potential of drama through nonverbal cues as a medium for character building.